2014
DOI: 10.2147/opth.s57640
|View full text |Cite
|
Sign up to set email alerts
|

Travoprost with sofZia® preservative system lowered intraocular pressure of Japanese normal tension glaucoma with minimal side effects

Abstract: BackgroundThis study aimed to evaluate the effect of travoprost with sofZia® preservative system for lowering the intraocular pressure (IOP) of Japanese normal tension glaucoma (NTG) patients.MethodsIn this prospective, multicenter, open-label study, Japanese NTG patients with baseline IOPs <20 mmHg were enrolled after three consecutive time measurements taken at screening and baseline visits. Travoprost with sofZia® was instilled once daily. Lowering effect on IOP, conjunctival hyperemia, superficial punctate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…14 Among the prostaglandin analog eye drops (bimatoprost, latanoprost, travoprost, and tafluprost), bimatoprost showed significantly strong IOP-lowering effects (Table 2). [15][16][17][18][19][20] Similar values of IOP reduction (12.0 ± 12.8%) were observed in the present study. Omidenepag isopropyl has been considered to have strong IOP lowering effects similar to prostaglandin analog eye drops in NTG patients.…”
Section: Discussionsupporting
confidence: 90%
“…14 Among the prostaglandin analog eye drops (bimatoprost, latanoprost, travoprost, and tafluprost), bimatoprost showed significantly strong IOP-lowering effects (Table 2). [15][16][17][18][19][20] Similar values of IOP reduction (12.0 ± 12.8%) were observed in the present study. Omidenepag isopropyl has been considered to have strong IOP lowering effects similar to prostaglandin analog eye drops in NTG patients.…”
Section: Discussionsupporting
confidence: 90%
“…Additional studies in NTG patients have shown a 20% reduction in diurnal IOP after timolol administered twice daily for 3 weeks [ 47 ], a 16% reduction in 24-h IOP after bimatoprost administered QD for 8 weeks [ 54 ], and a 24% reduction in IOP (mean of two daytime measurements) after bimatoprost administration QD for 2 weeks [ 55 ]. Studies with travoprost QD in NTG patients have shown an 11% reduction in mean IOP over 24 h after 4 weeks [ 56 ] and a 19.4% decrease in mean IOP measured within 2 h after drug administration in the evening after 12 weeks of treatment [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Category 1, there were three articles for latanoprost, 15 – 17 two articles for travoprost, 18 , 19 one article for bimatoprost, 20 five articles for tafluprost 21 – 25 ( Table 1 ), and 0 articles for unoprostone. In Category 2, the number of articles for each PGA was as follows: 14 for latanoprost, 15 , 16 , 26 37 seven for travoprost, 18 , 19 , 26 , 38 – 41 three for bimatoprost, 20 , 26 , 40 seven for tafluprost, 21 – 23 , 25 , 26 , 39 , 40 and 0 articles for unoprostone ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%